A novel carrier interleaved PWM method for four-level nested neutral-point-clamped inverters - Wei Zhou; Jupeng Pang; Mingzhe Wu; Chao Wang; Kui Wang; Yongdong Li (iEnergy)
The four-level nested neutral-point-clamped (4L-NNPC) inverter is a competitive topology among the various medium-voltage multilevel converters, and its main issue is flying-capacitor voltage unbalance. In this article, a novel carrier-interleaved pulse width modulation (CIPWM) method that satisfies the volt-sec balance principle is proposed with an advanced carrier distribution rule. By adopting the proposed CIPWM method, the redundant switching states of 4L-NNPC inverters can be evenly distributed into the output PWM waveform in each carrier period, and natural flying-capacitor voltage balance can be achieved. Furthermore, an active balancing strategy is also proposed to eliminate the voltage unbalance caused by nonideal factors, which is realized by simply adjusting the duty cycle and with no need to adjust the redundant switching states for 4L-NNPC inverters. The simulation and experimental results verify the effectiveness of the proposed CIPWM method and the flying-capacitor voltage balancing strategy.